Consolidated lung on contrast-enhanced chest CT: the use of spectral-detector computed tomography parameters in differentiating atelectasis and pneumonia. Issue 5 (May 2021) - Konietzke, Philip; Steentoft, Hauke H.; Wagner, Willi L.; Albers, Jonas; Dullin, Christian; Skornitzke, Stephan; Stiller, Wolfram; Weber, Tim F.; Kauczor, Hans-Ulrich; Wielpütz, Mark O.
Abstract: Objectives: To investigate the value of spectral-detector computed tomography (SDCT) parameters for the quantitative differentiation between atelectasis and pneumonia on contrast-enhanced chest CT. Material and methods: Sixty-three patients, 22 clinically diagnosed with pneumonia and 41 with atelectasis, underwent contrast-enhanced SDCT scans during the venous phase. CT numbers (Hounsfield Units [HU]) were measured on conventional reconstructions (CON120kVp ) and the iodine concentration (Ciodine, [mg/ml]), and effective atomic number (Zeff ) on spectral reconstructions, using region-of-interest (ROI) analysis. Receiver operating characteristics (ROC) and contrast-to-noise ratios (CNRs) were calculated to assess each reconstruction's potential to differentiate between atelectasis and pneumonia. Results: On contrast-enhanced SDCT, the difference between atelectasis and pneumonia was significant on CON120kVp, Ciodine, and Zeff images (p < 0.001). On CON120kVp images, a threshold of 81 HU achieved a sensitivity of 93 % and a specificity of 95 % for identifying pneumonia, while Ciodine and Zeff images reached the same sensitivity but lower specificities of 85 % and 83 %. CON120kVp images showed significantly higher CNRs between normal lung and atelectasis or pneumonia with 30.63 and 27.69 compared to Ciodine images with 3.54 and 1.27 and Zeff images with 4.22 and 7.63 (p < 0.001). None of the parameters could differentiate atelectasis and pneumonia without contrast media. Conclusions: Contrast-enhanced SDCT can differentiate atelectasis and pneumonia based on the spectral parameters Ciodine, and Zeff. However, they had no added value compared to CT number measurement on CON120kVp images. Furthermore, contrast media is still needed for a differentiation based on quantitative SDCT parameters. Highlights: Spectral CT parameters Ciodine and Zeff can differentiate atelectasis from pneumonia on contrast-enhanced images. Spectral CT parameters Ciodine and Zeff have no added value compared to CT number measurement on CON120kVp images. CNRs between normal and consolidated lung were higher on conventional on spectral images. Abstract : Pneumonia, Atelectasis, Diagnosis, SDCT